Genetic resistance to infectious diseases : A complementary tool to antimicrobial drugs in livestock? = La resistencia genética a las enfermedades infecciosas : ¿una herramienta complementaria a las drogas antimicrobianas en la producción pecuaria? - Rossetti, Carlos Alberto; Rossi, Ursula Amaranta (Elsevier, 2025)
A high percentage of the world's population depends on livestock for their sustenance. Therefore, animal health is closely linked to food safety and security, as it is essential to ensure that the food consumed is safe and not contaminated with pesticides, residues and microorganisms that pose a risk to public health. Traditionally, the control and eradication of infectious diseases on domestic animals have relied on the use of antibiotics and vaccines. Furthermore, sub-therapeutic doses of antimicrobials have been widely used as growth promoters in animal production. This overuse and misuse of antimicrobials in veterinary medicine has raised public concern and drawn attention to the livestock industry (including mammals, poultry and aquaculture) due to the development of antimicrobial-resistant zoonotic organisms and the presence of antimicrobial residues in animal products intended for human consumption.